Agama dari Revolusi Industri sampai Era Disrupsi - Ruslan Sudrajat (UIN Sunan Gunung Djati Bandung, 2022)
This research focuses on the historical development of the Industrial Revolution 1.0 as the beginning of the birth of another Industrial Revolution that sparked new emergence for other technological developments. Since the beginning, the Industrial Revolution has had a systematic, sequential scheme to create a new climate. It is connected to an era where old ways are replaced by new ways concentrated on digitizing every line of life, which is then called the era of disruption. The love of the era of disruption will certainly change the pattern of human life, where humans are creatures that contain beliefs or religion as the last defense they have in responding to change. The research method used in this research is a qualitative approach with a literature study. The data used in this study are primary and secondary data sources taken from books related to the investigation. According to Miles and Huberman, the analysis method was analyzed using the analysis method, which is broadly divided into three stages, namely data collection, data presentation, and concluding. The results of this study show that the history of the Industrial Revolution 1.0, which first occurred in the UK, has triggered various other Industrial revolutions that led to the creation of a socio-economic climate known as the current era of disruption.